Pilgrims ebook A nonfiction companion to magic tree house #27: thanksgiving on thursday. - Osborne, Mary Pope (Magic Tree House Fact Tracker, 2012)
Learn the true story of Thanksgiving with the #1 bestselling chapter book series of all time, Magic Tree House! Track the facts with Jack and Annie in this nonfiction companion to Magic Tree House #27: Thanksgiving on Thursday ! When Jack and Annie got back from their adventure in Magic Tree House #27: Thanksgiving on Thursday , they had lots of questions. What was it like to sail on the Mayflower? Why did the Pilgrims choose Plymouth? How did they survive in their new home? What did they really eat at the first Thanksgiving? Find out the answers to these questions and more as Jack and Annie track the facts. Filled with up-to-date information, photos, illustrations, and fun tidbits from Jack and Annie, the Magic Tree House Fact Trackers are the perfect way for kids to find out more about the topics they discovered in their favorite Magic Tree House adventures. And teachers can use Fact Trackers alongside their Magic Tree House fiction companions to meet common core text pairing needs. Did you know that there's a Magic Tree House book for every kid? Magic Tree House: Adventures with Jack and Annie, perfect for readers who are just beginning chapter books Merlin Missions: More challenging adventures for the experienced reader Super Edition: A longer and more dangerous adventure Fact Trackers: Nonfiction companions to your favorite Magic Tree House adventures Have more fun with Jack and Annie at MagicTreeHouse.com!